Contre-postcolonialité de Chateaubriand et Victor Hugo Discours littéraire et altérité minimale - Malela, Buata B. (Romanica Silesiana)
The present article examines the works of Chateaubriand (Itinéraire de Paris à Jérusalem) and Victor Hugo (Les Orientales and Bug-Jargal), focusing on what they reveal about Eastern and Caribbean “Otherness.” In other words, these two authors build a vision of the Other that can be positioned against postcolonialism, as the discourse they inscribe themselves in is characteristic of domination whose effects are a form of violence. Key words: Postcolonial studies, French literature, sociology of literature, philosophy of literature.